Chidamide Maintenance Therapy Following Induction Therapy in Patients With Peripheral T-Cell Lymphoma Who Are Ineligible for Autologous Stem Cell Transplantation: Case Series From China - Guo, Wei; Wang, Xingtong; Li, Jia; Yin, Xianying; Zhao, Yangzhi; Tang, Yang; Wang, Anna; Bai, Ou (Frontiers in Oncology, 2022)
Objective: To assess the potential benefit of chidamide maintenance therapy after induction treatment in peripheral T-cell lymphoma (PTCL). Materials and Methods: The clinical data of 48 transplantation-ineligible patients with different PTCL subtypes who received continuous chidamide treatment after first-line therapy were collected. Progression-free survival (PFS), overall survival (OS), and safety were analyzed. Results: In total, 68.8% of patients were male (33/48), the median age was 59.5 years (22~80). The pathological subtypes were angioimmunoblastic T-cell lymphoma (AITL, 43.8%), anaplastic large cell lymphoma (ALCL, 16.6%), PTCL-not otherwise specified (NOS, 25%), NK/T-cell lymphoma (NKT, 14.6%). 35.4% (7/48) patients had intermediate or high risk (IPI=3~5). 20 patients (41.7%) received chidamide as a maintenance treatment after achieving a complete response (CR). 57.1% (16/28) exhibited a better response after chidamide (9 cases partial response [PR] to CR, 7 from stable disease [SD] to PR). The CR and overall response rate (ORR) were 60.4% and 93.8%, respectively. In addition, 21/21 AITL, 10/12 PTCL-NOS, and 8/8 ALCL, 6/7 NK/T exhibited CR/PR as the best response during the follow-up period. Meanwhile, the CR and ORR did not differ by age (<60 vs ≥60: 50.0% vs 70.8%, P = 0.091; and 91.7% vs 95.8%, P = 0.551). The median follow-up period was 12.8 months (3.0–66.6), 14 patients developed PD (29.2%), 10 of them died of lymphoma (20.8%). Totally, the 40 cases achieved CR/PR from 1st line regimen got better PFS as well as OS than the rest 8 cases (the 1-year PFS was 80.8% vs 46.9% and the 2-year PFS was 71.9% vs 46.9%, P=0.012. the 1-year OS was 89.9% vs 72.6% and the 2-year OS was 85.9% vs 48.6%, P=0.032). No patients discontinued treatment because of adverse events. The most common toxicities were neutropenia (75.0%), anemia (79.2%), thrombocytopenia (58.3%), and anorexia (45.8%), and fatigue (43.8%). Conclusion: Chidamide maintenance therapy led to improvements of PFS and OS with a manageable safety profile in patients with PTCL. Further randomized studies are required to examine the role of chidamide maintenance therapy in PTCL.